Regulating the Intolerance of Contractual Breaches - Talavera Cano, Andrés (2016)
To penalize contractual breaches allows efficient allocation of risks in a contract, ensuring and maintaining the contractual equilibrium that the parties had in mind and shaped in its contractual regulation. The intelligent use of penalties will safeguard and maintain the economic balance of the contracts, thus maintaining the profitability of business operations pursued through them.